Das Protokoll des Lübecker Domkapitels 1544-1549 mit ergänzenden Texten - Prange, Wolfgang (Hamburg University Press, 2021)
The journals of the Lübeck cathedral chapter are handed down for the years 1523-1530, 1537-1540, and 1544-1549. They were kept in Latin and overwritten with "actus capitulares". The journals of the following decades have been lost. From 1583 on, the journals are preserved, but only fragmetnary. The latter were subsequently conducted in High German until the abolition of the chapter in 1804.This publication makestavailable the journal written in the years 1544-1549 by Johannes Tideman as Vizedekan and later as Dean. It is the 17th volume of the "Schleswig-Holsteinische Regesten und Urkunden" (SHRU), published by the Gesellschaft für Schleswig-Holsteinische Geschichte. it also is Vol. 107 of the series of the Publications of the Landesarchiv Schleswig-Holstein.From volume 11 on the SHRU devote themselves to the protocols of the Lübeck cathedral chapter.